Unusual cause of massive hemothorax: spontaneous rupture of nonfunctioning mediastinal paraganglioma - Lin, Feng; Liu, Chengwu; Ma, Lin; Pu, Qiang; Zhu, Yunke; Xiao, Zhilan; Guo, Chenglin; Zhang, Xiaolong; Li, Chuan; Liu, Lunxu (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Mediastinal paraganglioma is a rare neurogenic tumor with a hypervascular feature. The spontaneous rupture of mediastinal paraganglioma is an unusual cause of massive hemothorax. Here we present a case of 39-year-old man with massive hemothorax due to the spontaneous rupture of a mediastinal paraganglioma. The man underwent successful resection of tumor and had an uneventful recovery. To our knowledge, this is the first reported case of spontaneous rupture of nonfunctioning mediastinal paraganglioma.